(untitled) (Journal of economic and management development research, 2025)
Against the dual backdrop of the in-depth implementation of the innovation-driven development strategy and the accelerated construction of the Guangdong-Hong Kong-Macau Greater Bay Area, the value of intellectual property as a core intangible asset of technology enterprises has become increasingly prominent. Relying on the unique advantages of intensive sci-tech innovation resources and solid industrial foundation, Songshan Lake High-tech Zone has constructed a diversified, full-cycle, and efficient intellectual property financing system to address the industry pain points of technology enterprises characterized by "light assets, lack of collateral, and financing difficulties". Through literature research, case analysis, and data evidence, this paper systematically sorts out the development foundation and current characteristics of intellectual property financing in Songshan Lake, deeply analyzes its core practices in product innovation, mechanism coordination, policy empowerment, and ecosystem construction, quantitatively presents practical effects such as financing scale expansion, enterprise vitality stimulation, and industrial level enhancement, and extracts replicable and promotable experience and enlightenment. Research shows that through multi-party collaboration among government, banks, enterprises, and services, Songshan Lake has achieved the efficient transformation of intellectual property from "innovation achievements" to "financial assets". Its innovative practices provide an important reference paradigm for domestic similar high-tech zones to improve intellectual property financial services, solve financing difficulties of technology enterprises, and promote the deep integration of innovation chains, industrial chains, and capital chains.